The Changing Patterns of Investment in the PRC Economy - Carsten Holz (University of Hagen, Center for East Asia Macro-economic Studies (CEAMeS), 2017)
The investment-intensive growth model of the People's Republic of China (PRC) is often viewed as state-driven and ultimately unsustainable. But largely unnoticed, a shift has taken place. This paper examines the changes in investment patterns since 2003 and the potential impact of industrial policies on these patterns. The point of view is macroeconomic, based on economy-wide data with various breakdown. Significant shifts in investment patterns across sectors and ownership forms have occurred over time, supporting a new growth model with a reduced role of the state, and these shifts appear driven more by market factors than by government policies.
urn:nbn:de:hbz:708-dh4799
Keywords: E22; E6; L52; O11; O25; O53; 330; investment rate; investment policy; national investment strategy; sector distribution of investment; ownership distribution of investment; causes of investment; economic growth